An Earth Survey System Design using the Kappa-8 Rocket - Andi Sadewo Salatun (Institute for Research and Community Services (LPPM) ITB, 1979)
Abstract. This paper describes the design of the earth survey system by using available rocket and ground supporting unit at LAPAN. The basic concept of the system is to carry a camera on essentially vertical trajectory to a very high altitude from which a wide area can be photographed. The camera is switched on near to the maximum altitude heading toward the required area and recovered by parachute. The design requirements in this system are to provide a stable and controllable payload to enable the camera to point to the required direction and to provide a camera unit equipped with the logic control switch giving the desired picture resolution. Because of the design simplicity and low cost, this system can be developed in Indonesia which in turn will be useful for Remote Sensing activity and also will give a better experience in designing, fabricating and handling the attitude control payload at LAPAN. Sari. Di sini akan dipaparkan disain dari suatu sistem pengamat permukaan bumi dengan menggunakan roket dan ground facility yang dipunyai LAPAN saat ini. Prinsip dasar dari sistem ini adalah menerbangkan sebuah roket yang dilengkapi dengan kamera sampai ketinggian 200 km di mana permukaan bumi yang luas dapat difoto. Kamera di